Expression of RAD51 and Its Clinical Impact in Oral Squamous Cell Carcinoma - Yuyang Li; Jia Li; Jingchun Sun; Yingkun Liu; Dingkun Liu; Liuyi Du; Bizhou Wang; Weiwei Liu (Analytical Cellular Pathology)
Purpose. To examine the expression of RAD51 in oral squamous cell carcinoma (OSCC) and analyze its connection with pathological grade, clinical stage, and lymphatic metastasis potential. Methods. For this study, 74 OSCC samples, 15 normal mucosa tissues, and 11 normal skin tissue samples were collected. RAD51 expression was investigated using immunohistochemistry. A follow-up visit was used to assess the prognosis of each patient. We compared RAD51 expression in oral mucosa epithelial cells (OMECs), keratinocytes, and tongue squamous cell carcinoma cells (TSCCs) by Western blot analysis. Results. RAD51 expression was higher in tumor cells than in normal mucosal tissues. In addition, RAD51 expression was associated with higher tumor differentiation (P<0.05). Also, RAD51 expression was higher (P<0.05) in patients with lymphatic metastases, and relapse rates were also higher in patients with elevated RAD51 levels (P=0.052). In addition, RAD51 expression levels were highest in the skin keratinocytes, followed by the TSCCs and OMECs. Conclusion. A strong positive correlation was found between RAD51 expression and the degree of malignancy in OSCC patients, suggesting that RAD51 could be an excellent prognostic indicator for OSCC patients.